Estudo das concentrações e limites de referência dos hormônios tireoideanos nos três trimestres da gestação normal: ação da HCG sobre o TSH e FT4 - Carvalho Neto, Calil (2000)
Among the complications of the gestational cycle, thyroid diseases are undoubtedly one of the endocrine pathologies that most affect women of reproductive age (GLINOER, 1997; HANNA et al., 1998). The correlation between pregnancy and functional thyroid changes has long been recognized. During pregnancy, there is evidence that the functional dynamics of this gland is altered, affecting virtually all aspects of the thyroid hormone economy, reflecting greater metabolic demand (ROMALDINI, 1983). In turn, thyroid hyper or hypofunction can compromise the woman's fertility and contribute to greatly reduce fetal survival and development (ROMALDINI, 1983; GIROUX et al, 1997). All thyroid diseases, which are most prevalent in females, are found during pregnancy. In this case, the clinical picture of thyroid diseases is difficult to diagnose and the study of glandular function through the measurement of thyroid hormones is of fundamental importance (BISHNOI and SACHMECHI, ​​1996). sludge and amino acids are essential substrates to form thyroid hormones (ROMALDINI, 1983). Iodine, in the form of iodide, reaches the body by eating food and water, the main sources of this element in nature; it is absorbed by the gastrointestinal tract, on average 60pg daily (KRZYCZKOWSKA-SENDRAKOWSKA et al., 1993; WOHLLK et al., 1993; KABYEMELA et al., 1996; BACZYK et al., 1997), being found in plasma in concentrations from 0.18 to 0.4 gg / ml (DOWLING et al, 1967); of the extravascular space, 30% are concentrated in the thyroid and the remaining 70% are distributed in the extrathyroidal “pole”, being excreted by the kidneys. The renal clearance of iodine is 35 ml / minute and the thyroid is 17 ml / minute (DAVISON, 1983; DAFNIS and SABATINl, 1992). Approximately 95% of the total iodide stored in the body is found in the thyroid and the remaining 5% circulates as hormones in plasma and tissues. The entry of iodide into the thyroid is carried out actively through the iodine pump, correlated to the ATPase NA +, K * system, dependent; this pump is stimulated by pituitary thyrotrophin (TSH) and the low concentration of iodine in the plasma, being inhibited by certain ions such as thiocyanate and perchlorate (INGBAR, 1988). After transport into the thyroid follicular cell, the iodide enters a series of reactions, which, in the end, lead to the synthesis of active thyroid hormones (TAUROG, 1978). The first of these reactions involves the oxidation of iodide in the presence of peroxidase, an enzyme capable of using hydrogen peroxide generated by the oxidation of the pyridine triphosphorus nucleotide hydrogenase (TPNH). The intermediate compound formed, the iodine of greater valence (l +), binds quickly to position three of the tyrosine molecule, present in the peptide chain of thyroglobulin, forming mono-iodotyrosine (MIT); the incorporation of another iodine atom at position 5, forms diiodotyrosine (DIT) (ROMALDINI, 1983). The way in which thyroid hormone synthesis occurs "in vivo" is still unknown. Two hypotheses received the main attention (TAUROG, 1978), according to the first, thyroxine and 3, 5, 3 'triiodothyronine are formed by the interaction of a peptide-bound DIT with an oxidation product from DIT or MIT, respectively; in the case of DIT, the suggested product is 3, 5 - diiodine-4-hydroxy-phenylpyruvic acid (TAUROG, 1978). The most considered point of view differs from the above in that it requires the coupling of two iodothyronines. Thus, by the association of a molecule of DIT and another of MIT, 3, 5, 3 'tri-iodothyronine (T3) and, to a small extent, 3, 5', 3 'reverse tri-iodothyronine (rT3) are formed (De GROOT et al., 1972; CHOPRA, 1976). The coupling of two DIT molecules forms tetraiodothyronine or thyroxine (De GROOT et al., 1972). Thyroglobulin, a glycoprotein with a molecular weight of 660,000 and a sedimentation constant of 19 S, constitutes the repository of all thyroxine, triiodothyronine and most of the MIT and DIT (ROBBINS et al., 1978). Its secretion occurs normally by the thyroid gland, being found in small amounts (1 to 27 ng / ml) in the serum of normal individuals (Van HERLE et al., 1973; PINCHERA et al., 1977; PACINI et al, 1980). Thyroid hormones are secreted under TSH stimulus that activates the uptake of thyroglobulin droplets by the pseudopods of the apical margin of the follicular cell, which will coalesce with lysosomes containing peptidases and proteases, enzymes capable of degrading thyroglobulin to release T4, T3, rT3, l 'and small concentrations of iodotyrosins (ALPERS et al., 1955; De GROOT et al., 1972; CHOPRA, 1976; WU et al., 1976; MACIEL et al., 1979).